Role of Molecular Breeding in Genetic Improvement of Pigeonpea - Kumar Magadum, Santosh; Duggi, Shrishail; Gangapur, Doddabhimappa; Verma, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Advances in molecular breeding tools and approaches in pigeonpea have allowed addressing many significantly scientific questions that are impossible to do so before. Recent progress in the development of genome-scale data sets for pigeonpea offers important new possibilities for crop improvement. This progress will enable biotechnologists to more rapidly and precisely target genes that underlie key agronomic traits. Among the most important agronomic targets are a series of abiotic and biotic stresses that limit crop productivity. Molecular analysis of germplasm collections with new-generation genomic tools will accelerate trait discovery through methods such as linkage and association mapping. Use of molecular markers in diverse mapping populations in pigeonpea will facilitate the construction of a genetic map, mapping, and map based cloning of disease resistance genes, quantitative trait loci (QTL) mapping, and the integration of phenotypic data across the different mapping populations. Moreover, organized genome resources, including physical maps and functional genomics tools, will facilitate the isolation of genes for resistance or tolerance to biotic and abiotic stresses. Molecular markers identified from these approaches that are associated with traits of importance to breeders should accelerate pigeonpea improvement via marker assisted selection (MAS) or transgenic approaches. Ultimately the availability of high-throughput and cost-effective genotyping platforms, combined with automation in phenotyping methodologies, will increase the uptake of genomic tools into breeding programs, and thus usher in an era of genomics-enabled molecular breeding in these legumes. Modern molecular breeding methods together with the power of genomics and genetic resources developed will revolutionize pigeonpea crop improvement, and consequently benefit farmers and consumers of this important pulse crop of India and the semi-arid regions of the world.